Characterization of Syrian Nano metric Zeolite Ore Modified by Using Cationic Surfactant (Hexadecyltrimethyl Ammonium Bromide = HDTMA-Br) (Latakia University Journal -Biological Sciences Series, 2022)
The objective of this research was to study the possibility of modifying physicochemical properties of Syrian Natural zeolite ore (NZ) and characterization it, in order to improve its capacity to bind anionic metals such as phosphate. Modification process executed by grinding zeolite to Nano scale, then the external surface was modified by the use of cationic surfactant Hexadecyltrimethyl ammonium bromide) HDTMA-Br). Surfactant modified Nano zeolites (SMNZ) were prepared by treatment of crushed natural zeolite with graduated concentrations of surface surfactant HDTMA-Br in order to achieve three rates of surface modification levels 50, 100 and 200% of NZ-ECEC, which equal to 26.5 meq/100g. Some chemical and mineralogical structure of NZ and modified (SMNZ) were studied by the use of many techniques such as (AFM), (SEM), and (FTIR). AFM images demonstrate that mean diameter of grinded zeolite were between 10 and 60 nanometer, which indicate that grinding process was successful to achieve the nanoscale granules. also SEM images demonstrate mainly the presence of Phillipsite and Analsim as a dominate zeolitic minerals in NZ samples, surface modification of NZ led to absence of clear edge of zeolite grains due to the application of surfactant material. FTIR spectroscopy analysis of (SMNZ) sample showed successful placement of surfactant on NZ Phosphate. Adsorption results showed that SMNZ capable to remove 89% of phosphate in solution, this demonstrate that surface modification of NZ was successful.